Pengembangan Media Komik Digital Berbasis Canva untuk Siswa Kelas XI SMA Masa Depan Cerah Surabaya - Rudiyanto, Catur; Huda, Nuril; Tobing, Victor Maruli L. (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
The aim of this research is to create digital comic media using the Canva application. This study follows a research and development (R&D) approach and utilizes the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation. The participants included one history teacher and 19 students who actively engaged in daily teaching and learning activities, along with one material expert and one media expert. Data was collected through observations, questionnaires, interviews, and tests. The findings indicate that the digital comic media based on the Canva application is rated as "Very Feasible." The feasibility percentages were as follows: media experts rated it at 87% ("Very Feasible"), material experts at 85% ("Very Feasible"), education practitioners (teachers) at 95% ("Very Practical"), and educational practitioners (students) at 93% ("Very Practical"). Furthermore, student learning outcomes improved significantly after utilizing the digital comic media, achieving a post-test score of 90%, which is categorized as "Effective."